Application of XRF Scanning to Different Geological Archives. Issue 9 (16th September 2021) - Guo, Fei; Clemens, Steven; Liu, Xingxing; Long, Yili; Li, Dong; Tan, Liangcheng; Liu, Chengcheng; Yan, Hong; Sun, Youbin
Abstract: High‐resolution XRF scanning is widely used on marine and lake sediment cores as a means of rapidly acquiring elemental concentrations from closely spaced intervals with no damage to the samples. Therefore, guidance on how to obtain reliable datasets and select suitable step sizes for different geological media are of great importance. Here we apply this efficient analytical method to loess, stalagmite, and tridacna samples. The results show that 11 elements (Al, Si, K, Ca, Ti, Mn, Fe, Rb, Sr, Zr, and Ba), eight elements (Ca, Si, K, Fe, Cu, Ni, Sc, and Sr) and seven elements (Ca, Sr, Cu, Fe, Sc, Ni, and Si) can be robustly detected by this method for loess, stalagmite and tridacna archives respectively, demonstrating the capacity to reconstruct high‐resolution paleoclimate changes. For loess cores, efficiency emission decay of the X‐ray tube, water content, matrix, and grain size effects are the main factors influencing elemental intensities. The efficiency emission decay of the X‐ray tube, scanning path, scanning interval, and radiation area have a significant effect on element intensities of stalagmite and tridacna samples. Based on our investigations, we suggest optimal resolutions for scanning these three archives for millennial to seasonal‐scale paleoclimatic reconstructions. We compare our analyses with existing results from traditional (discrete) analyses, demonstrating similar scales of variability. Our results suggest that geochemical proxies measured by XRF scanning, such as Rb/Sr, Zr/Rb, and Ca/Ti ratios of loess and the Sr/Ca ratio of speleothem and tridacna, can be effectively used to reconstruct high‐resolution paleoclimate changes. Key Points: Confirming which elements can be robustly detected for loess, stalagmite, and tridacna using high‐resolution XRF scanning Optimal scanning resolutions are suggested for three archives on millennial to interannual‐scale paleoclimatic reconstructions Elemental ratios tested by XRF scanning have great potential for reconstructing paleoclimate changes across a range of timescales